Multimodality Evaluation of Aortic Insufficiency and Aortitis in Rheumatologic Diseases - Choi, Eunjung; Mathews, Lena M.; Paik, Julie; Corretti, Mary C.; Wu, Katherine C.; Michos, Erin D.; Hays, Allison G.; Mukherjee, Monica (Frontiers in Cardiovascular Medicine, 2022)
Aortic insufficiency is commonly observed in rheumatologic diseases such as ankylosing spondylitis, systemic lupus erythematosus, antiphospholipid syndrome, Behçet’s disease, granulomatosis with polyangiitis, and Takayasu arteritis. Aortic insufficiency with an underlying rheumatologic disease may be caused by a primary valve pathology (leaflet destruction, prolapse or restriction), annular dilatation due to associated aortitis or a combination of both. Early recognition of characteristic valve and aorta morphology on cardiac imaging has both diagnostic and prognostic importance. Currently, echocardiography remains the primary diagnostic tool for aortic insufficiency. Complementary use of computed tomography, cardiac magnetic resonance imaging and positron emission tomography in these systemic conditions may augment the assessment of underlying mechanism, disease severity and identification of relevant nonvalvular/extracardiac pathology. We aim to review common rheumatologic diseases associated with aortic insufficiency and describe their imaging findings that have been reported in the literature.